Pengaruh Promosi Program Studi Ilmu Komunikasi terhadap Minat Mendaftar Mahasiswa Ilmu Komunikasi Universitas Mbojo Bima - Erika Fajar Subhekti; Irham Irham; Rahmi Rahmi; Erick Fajar Subhekti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Promotion is one way to introduce products or services owned by a person or a company. Promotion is used by campuses to show the image of the campus to a large audience. Promotion is one of the factors that influence student interest in registering at a university. Data from the Communication Science Study Program at Mbojo Bima University shows a decrease in the number of students, which previously had 92 students and then in the following year only 67 students. This study aims to determine whether there is an influence of the promotion of the Communication Science Study Program on the interest in registering Communication Science students at Mbojo Bima University. This research is quantitative research, with a sample of 75 samples calculated using the slovin formula. The research instruments used were Likert scales and questionnaires. Data analysis using the chi square test SPSS version 25.00. The results of the study were that there was an effect of the promotion of the Communication Science Study Program on the interest in registering Communication Science students at Mbojo Bima University by 56.1%. Promotion carried out by the Communication Science Study Program must be maintained or if necessary increased again so that the Communication Science Study Program at Mbojo Bima University can be known to a large audience.